Impact of thermal denaturation on renal volume reduction after partial nephrectomy using soft coagulation hemostasis - Ibuki Tsuru; Masashi Kusakabe; Taro Izumi; Akihiro Ono; Yasuko Muraki; Taro Teshima; Ryo Amakawa; Yasushi Inoue; Tadashi Yoshimatsu; Teppei Morikawa; Haruki Kume; Shuji Kameyama; et al. (Scientific Reports)
Abstract Partial nephrectomy has become the gold standard treatment for small renal masses. This study aimed to assess the impact of soft coagulation hemostasis on parenchymal volume reduction of the operated kidney after an open partial nephrectomy. We retrospectively reviewed 94 patients with small renal tumors who underwent open partial nephrectomy with soft-coagulation hemostasis at our institution. We measured the preoperative and postoperative renal volumes by computed tomography (CT) and calculated the renal volume reduction ratio as postoperative volume/preoperative volume. We performed multivariate analysis to identify the predictors of renal volume reduction. The median renal volume ratio was 0.75, and the median renal volume reduction rate was − 2.49 cm3/month (IQR, − 3.33 to − 1.59). The RENAL score was inversely associated with ipsilateral renal volume reduction. In multivariate analysis, RENAL score, and tumor size were independent predictors of postoperative renal volume reduction. Soft coagulation hemostasis may influence the postoperative renal volume after partial nephrectomy, especially in patients with complex tumors.